The Industrial Bourgeoisie in the Publications of the National Society of Industries during the "Aristocratic Republic" - Sato Kuroda, Enrique (2006)
The article presents some approaches to the emergence of the industrial bourgeoisie in the country, developed from a review of the first publications of the National Society of Industries at the end of the 19th century and the beginning of the 20th century, and in particular of its official spokesman " The industry".